2021
DOI: 10.3390/jmse10010024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of the Performance of Dynamic Wing for Augmenting Ship Propulsion in Head and Quartering Seas

Abstract: Flapping-foil thrusters arranged at the bow of the ship are examined for the exploitation of energy from wave motions by direct conversion to useful propulsive power, offering at the same time dynamic stability and reduction of added wave resistance. In the present work, the system consisting of the ship and an actively controlled wing located in front of its bow is examined in irregular waves. Frequency-domain seakeeping analysis is used for the estimation of ship-foil responses and compared against experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The pitching mechanism of the foil presents an interesting design consideration. Previous research has investigated the use of fixed foils (Bockmann et al, 2018;Feng et al, 2014;Huang et al, 2016), passively spring loaded foils (Bockmann and Steen, 2014;Bowker and Townsend, 2022) and actively pitched foils (Belibassakis and Politis, 2013;Belibassakis and Filippas, 2015;Bockmann and Steen, 2014;Huang et al, 2016;Belibassakis et al, 2022). In comparison to previous studies (Feng et al, 2014;Bockmann et al, 2018), the foil size implemented for this assessment is relatively large, which is considered beneficial for maximising efficiency but costly for structural design and the feasibility of retraction.…”
Section: Limitationsmentioning
confidence: 99%
“…The pitching mechanism of the foil presents an interesting design consideration. Previous research has investigated the use of fixed foils (Bockmann et al, 2018;Feng et al, 2014;Huang et al, 2016), passively spring loaded foils (Bockmann and Steen, 2014;Bowker and Townsend, 2022) and actively pitched foils (Belibassakis and Politis, 2013;Belibassakis and Filippas, 2015;Bockmann and Steen, 2014;Huang et al, 2016;Belibassakis et al, 2022). In comparison to previous studies (Feng et al, 2014;Bockmann et al, 2018), the foil size implemented for this assessment is relatively large, which is considered beneficial for maximising efficiency but costly for structural design and the feasibility of retraction.…”
Section: Limitationsmentioning
confidence: 99%
“…More recently, in Filippas et al [32], in-house GPU-BEM and HPC-RANSE solvers were developed to further investigate the performance of active flapping foils propulsion for augmentation of ship prolusion, focusing on freesurface, irregular wave, and viscosity effects. Then, Kostas Belibassakis et al [33] completed laboratory model testing of the bio-mimetic thruster with active control at the towing tank of National Technical University of Athens (NTUA) with ship hull models of specific type. The results showed that the additional thrust generated by the dynamic foil enabled the engine to operate in part-load without compromising vessel speed, resulting in an additional positive effect on the emission profile.…”
Section: Investigations Regarding Bow Foilmentioning
confidence: 99%
“…To sum up, the research on the hydrodynamic problems of bow foil wave-augmented propulsion system has mainly focused on the following aspects: First, numerical prediction on the coupling effect of hydrofoil and wave [9,26,36] includes the influence of a series of parameters; immersion depth of hydrofoil and free surface effects [32,36]; phase difference between waves and hydrofoil; size, location, geometry, and number of hydrofoils [20,34]; and oblique waves [33,34]. The research in this area is relatively mature and can be used as the basis for studying interaction and coupling between waves, oscillating foils, and hull.…”
Section: Investigations Regarding Bow Foilmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowker et al 22 presented a time-domain numerical model and experimental results from a wave-powered ASV prototype with forward and after flapping foils. Belibassakis et al 23 studied a device that can directly use the wave energy to push the ship forward by installing hydrofoils on the ship, and the results show that the device has good performance. Zhang et al 24 established a multi-body dynamic model for wave-driven catamaran, through numerical simulation, the hydrodynamic response is identified and comprehensively analyzed.…”
Section: Introductionmentioning
confidence: 99%